An In-vitro Comparison of Force Loss of Orthodontic Non-Latex Elastics. - Shiva Alavi; Atusa Rahnama Tabatabaie; Fatemeh Hajizadeh; Alireza Haerian Ardekani (Tehran University of Medical Sciences, 2014)
The amount and consistency of the applied forces to the tooth are important factors in tooth movements; therefore, the aim of this study was to compare the initial force and the force loss of three brands of elastics in 24 hours.In this in-vitro study sixty non-latex elastics (3/16 medium) from three companies (Forestadent, Dentaurum and Ortho Technology) were randomly selected. Two static tests were performed, the first in a dry environment to evaluate the initial force and the other performed in a wet environment (artificial saliva) to evaluate the force loss in 24 hours. The Universal testing machine measured the forces after stretching the elastics to three times the lumen diameter. Data were analyzed by repeated measures ANOVA, One-way ANOVA, Tukey-HSD, Paired samples test, and one sample test.The difference between the brands was significant (p=0.002). Force loss was observed in all samples; 4-7.5% force loss occurred after one hour and 19-38% force loss occurred after 24 hours. The average initial force of Forestadent and Ortho Technology was significantly higher than marketed forces (pDentaurum>Ortho-Technology. According to the initial force and force loss percentage it is suggested to replace the non-latex elastics several times a day.